Does Technological Innovation Promote Haze Pollution Control? New Evidence Based on Panel Threshold Model and Spatial Econometric Model - Shi, Weiwei; Zhang, Lin (Frontiers in Environmental Science, 2022)
Since the reform and opening-up, China's rapid economic growth mainly depends on the industrial development mode of "high energy consumption and high pollution", which has caused serious haze pollution. In order achieve the goal of haze control and sustainable development, we need to give full play to the role of technological innovation. Empirical analysis of haze control effect of technological innovation has theoretical significance and practical value. Based on the panel data of 30 provinces in China from 2005 to 2018 and the PM2.5 concentration data published by the atmospheric composition analysis group of Dahlhouse University, this paper selects R&D personnel input and technology market turnover to represent the level of technological innovation, and uses panel data model, threshold effect model and spatial Durbin model to empirically analyze the impact of technological innovation on haze pollution control. The empirical results show that: (1) technological innovation can significantly reduce the PM2.5 concentration of the province, showing a positive haze control effect; (2) Technological innovation indicates a negative indirect effect on PM2.5 concentration, confirming the "technology spillover effect", that is, technological innovation also has haze control effect on the surrounding provinces; (3) With the increase of the province's economic aggregate, the haze control effect of technological innovation shows a trend of "high-low-high", and the role of technological innovation is the lowest in the stage of economic transformation; (4) From the perspective of regional differentiation, the haze control effect of technological innovation is the largest in the central region, and the smallest in the western region. Technological innovation indicates positive haze control effect on all regions at all stages of economic development. This paper provides policy suggestions for the government and enterprises to use innovation for cleaner production and sustainable development.